Patterns of social reciprocal relationship in a central Panay rural community. - Lagrosa, Suzette Leysa
Mutual exchange of obligation among kins and friends in a rural Philippine community has long been an existing value system. However, with societal changes taking place in the rural Philippines, values have been altered. This study of reciprocal relationships is a detailed example of how mutual exchange of obligation is taking place in the rural community of Buwang in Lambunao (Iloilo)., This study specifically aims to (1) describe the patterns of social reciprocal relationship in a rural community, (2) describe the patterns of vertical and horizontal relationships, and (3) find ways by which people involved in the exchange maintain it. This is a descriptive study so simple frequency counts and percentage are used in analyzing the data. The results of the study showed that people in the community exchange more favors with people who live near them. The favors exchanged range from personal goods to services. People with the same social status also exchange more frequently than people with different statuses. And lastly, those involved in the reciprocal relationship maintain it through constant interaction such as friendly visits and afternoon gatherings in places such as sari-sari stores, the river, the field and others.